Strategi Keberlanjutan Pola Nafkah Rumah Tangga Petani Padi Pulu Mandoti di Desa Salukan, Kabupaten Enrekang - Andi Maslia Tenrisau Adam; Mais Ilsan; Rasmeidah Rasyid; Az-Zahrah Faharuddin (Jurnal Ilmu Pertanian Indonesia, 2024)
Pulu mandoti is a local type of rice that is fragrant and rare. This glutinous rice has a high selling price and can only thrive when planted in Salukanan Village. However, its productivity is still relatively low, so efforts are needed to sustain the farming business. This study aims to analyze farmer households' livelihood patterns and sustainability strategies. The respondents were 50 farmers selected using simple random sampling. The data were analyzed in descriptive, qualitative, and quantitative ways. The results showed that the pattern strategy of pulu mandoti rice farmer households is an intensification and extensification strategy in agricultural landuse, and diversification strategies in the livestock, service, trade, and employment sectors. The sustainability of farming livelihood patterns resulted in an index of 89.66%, included in the sustainable category. The government needs to pay attention to production factors that affect the productivity of pulu mandoti rice farming so that farming can be sustainable. Keywords: diversification strategy, extensification and intensification, livelihood pattern, pulu mandoti, rice production